Responsible Mineral Resource Development: The Way Forward - H., Termidi; Aainaa Izyan, Nafsun; Anwaruddin, Hisyam (Penerbit Universiti Malaysia Pahang, 2017)
This paper provides an insight to a responsible mining, whereby it is an effective application of sustainability concepts to the full mining life cycle. Responsible mining refers to advocacy to reform mining activity, as well as to a marketing strategy used by mining companies to promote their operations as environmentally or socially sound. The author explains the ASEAN principles of responsible mineral resource development, the reporting mechanism and criteria in ASEAN countries responsible mining framework.